Photoautotrophic Batch Cultivation of Limnospira (Spirulina) platensis: Optimizing Biomass Productivity and Bioactive Compound Synthesis Through Salinity and pH Modulation - Matteo Rizzoli; Giovanni Antonio Lutzu; Luca Usai; Giacomo Fais; Debora Dessì; Robinson Soto-Ramirez; Bartolomeo Cosenza; Alessandro Concas (Marine Drugs, 2025)
This study investigates the effects of salinity and pH modulation on the growth, biochemical composition, and bioactive compound production of Limnospira platensis under photoautotrophic batch cultivation. Cultures were grown in cylindrical photobioreactors using modified Jourdan medium, with controlled variations in NaCl concentrations (0.2–10 g L−1) and pH levels (9–11) to simulate moderate environmental stress. Maximum biomass productivity (1.596 g L−1) was achieved at pH 11 with 10 g L−1 NaCl, indicating that L. platensis can tolerate elevated stress conditions. Phycocyanin (PC) content peaked at 9.54 g 100 g−1 dry weight (DW) at pH 10 and 5 g L−1 NaCl, triple the value at pH 9, highlighting optimal physiological conditions for pigment synthesis. Protein fraction dominated biomass composition (40–60%), while total lipid content increased significantly under high pH and salinity. Polyphenol content reached 19.5 mg gallic acid equivalents (GAE) gDW−1 at pH 10 with 0.2 g L−1 NaCl, correlating with the highest antioxidant activity (Trolox equivalent antioxidant capacity). These findings underscore the potential of L. platensis as a valuable source of proteins, pigments, and antioxidants, and emphasize the utility of moderate environmental stress in enhancing biomass quality, defined by protein, pigment, and antioxidant enrichment. While this study focused on physiological responses, future research will apply omics approaches to elucidate stress-response mechanisms. This study provides insights into optimizing cultivation strategies for large-scale production exploitable in food, pharmaceutical, and bio-based industries.